Harvard encyclopedia of American ethnic groups - Thernstrom, Stephan (Cambridge, Mass. : Belknap Press of Harvard University, 1980)
Informative and entertaining, this volume is an indispensable reference work for home, library, and office. It establishes a foundation for the burgeoning field of ethnic studies; it will satisfy and stimulate the popular interest in ancestry and heritage. It is a guide to the history, culture, and distinctive characteristics of the more than 100 ethnic groups who live in the United States. This is a comprehensive guide to more than 100 American groups with ethnic, religious, cultural, or regional identities. In addition there are almost 30 essays on related issues. For each signed group entry, the entire range of experience is discussed from the group's origins, migration, arrival and settlement, to its economic, social, cultural, religious life, and its experiences with education and politics. Maps and tables are included. This is a standard source, though now somewhat limited, especially for Asian peoples. Recommended for high school collections. This is a comprehensive guide to more than 100 American groups with ethnic, religious, cultural, or regional identities. In addition there are almost 30 essays on related issues. For each signed group entry, the entire range of experience is discussed from the group's origins, migration, arrival and settlement, to its economic, social, cultural, religious life, and its experiences with education and politics. Maps and tables are included. This is a standard source, though now somewhat limited, especially for Asian peoples. Recommended for high school collections.
Machine derived contents note.
Includes bibliographical references.
Includes bibliographies.
Keywords: Minorities -- United States -- Dictionaries; Ethnicity -- United States -- Dictionaries; United States -- Ethnic relations -- Dictionaries; United States -- Ethnic minorities -- Encyclopaedias